2009 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) 2009
DOI: 10.1109/vlhcc.2009.5295258
|View full text |Cite
|
Sign up to set email alerts
|

Combining spatial and semantic label analysis

Abstract: Labels in spreadsheets can be exploited for finding errors in spreadsheet formulas. Previous approaches have either used the positional information of labels or their interpretation as dimension for checking the consistency of formulas.In this paper we demonstrate how these two approaches can be combined. We have formalized a combined reasoning system and have implemented a corresponding prototype system. We have evaluated the system on the EUSES spreadsheet corpus. The evaluation has demonstrated that adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous research [8] has shown that the majority of dimensions are found on only one axis. Specifically, only 128 out of the 567 tables in the investigated spreadsheets contained dimensions on more than one axis.…”
Section: Ucheck Enhanced With Dimension Inferencementioning
confidence: 92%
See 4 more Smart Citations
“…Previous research [8] has shown that the majority of dimensions are found on only one axis. Specifically, only 128 out of the 567 tables in the investigated spreadsheets contained dimensions on more than one axis.…”
Section: Ucheck Enhanced With Dimension Inferencementioning
confidence: 92%
“…While the method described in the previous section has been shown to be effective at detecting errors in spreadsheets [8], it is but one way to combine these labels and dimensions. In fact, this system was designed only as an add on to the dimension inference system, and so in some cases it ignores the search for label errors to focus instead on identifying dimension errors.…”
Section: Dimension Instantiationmentioning
confidence: 99%
See 3 more Smart Citations